1996
DOI: 10.1007/bf02550974
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumour markers in renal failure

Abstract: In order to assess the clinical value of six tumour markers in pre-dialysis patients with chronic renal failure as well as in patients on regular haemodialysis, we studied these markers in 35 predialysis patients, 35 patients on chronic haemodialysis and 35 healthy controls. Serum squamous cell antigen (SCC), CA 19.9, and CA 125 levels were found to be elevated in the uraemic groups as compared to the normal controls. Carcinoembryonic antigen (CEA), alpha foetoprotein (AFP), and prostate-specific antigen (PSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 15 publications
3
30
0
1
Order By: Relevance
“…The calculation of PSA levels, which has been applied in the general population as a marker of prostate cancer with relative success, has not been proven to be of the same value in the hemodialysis patients. Previous studies have not shown differences in PSA levels between hemodialysis male patients and the general population [7, 8, 9, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…The calculation of PSA levels, which has been applied in the general population as a marker of prostate cancer with relative success, has not been proven to be of the same value in the hemodialysis patients. Previous studies have not shown differences in PSA levels between hemodialysis male patients and the general population [7, 8, 9, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…Like all other cancer markers, CA 125 has a restricted diagnostic value [1]. Elevated serum CA 125 levels have been demonstrated in a number of benign gynecologic as well as benign and malignant nongynecologic conditions [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Im Rah men der Hä modia ly se wer den in Ab hän gig keit von der ver wen de ten Ka pil la re, Pro te i ne von ei ner Grö ße um 7000 Da (CVV HD, kon ti nuier li che ve no ve nö se Hä mo dia ly se) bis zu ei ner Grö ße um 66.000 Da ("High-fluxMem bra nen") dia ly siert. Bei der Pe ri toneal dia ly se be trägt die se Grö ße 70.000 Da [29,30,31,32,33,34].…”
Section: Psa-wert Und Nie Re N Er Satz the Ra Pieunclassified